Nicaraguan and US nursing collaborative evaluation study: Identifying similarities and differences between US and Nicaraguan curricula and teaching modalities using the community engagement model. (April 2017) - Lake, Donna; Engelke, Martha K.; Kosko, Debra A.; Roberson, Donna W; Jaime, Joba Fany; López, Feliciana Rojas; Rivas, Fidelia Mercedes Poveda; Salazar, Yolanda Matute; Salmeron, Juana Julia
Abstract: Background: Curricula evaluation is an essential phase of curriculum development. Study describes the implementation of a formative evaluation used by faculty members between Universidad Nacional Autonóma de Nicaragua (UNAN-Leon) Escuela de Enfermeriá, Nicaragua and East Carolina University College of Nursing (ECU CON) in North Carolina, US. Objectives: Program evaluation study to conduct an assessment, comparison of a medical-surgical adult curriculum and teaching modalities. Also, explore the Community Engagement (CE) Model to build a Central American-US faculty partnership. Design: Methodological evaluation study utilizing a newly developed International Nursing Education Curriculum Evaluation Tool related to adult medical and surgical nursing standards. Also, the CE Model was tested as a facilitation tool in building partnerships between nurse educators. Data: Nicaragua and US nursing faculty teams constructed the curriculum evaluation by utilizing the International Nursing Education Curriculum Evaluation Tool (INECET) by reviewing 57 elements covering 6 Domains related to adult medical and surgical nursing standards. Methods: Developed, explored the utilization of the INECET based on a standard of practice framework. The Community Engagement Model, a fivephase cycle, Inform, Consult, Involve, Collaborate, and Empower was utilized to facilitate the collaborative process. Results: Similarities between the US and Nicaraguan curricula and teaching modalities were reflective based on the 57 elements covering 6 Domain assessment tool. Case studies, lecture, and clinical hospital rotations were utilized as teaching modalities. Both schools lacked sufficient time for clinical practicum time. The differences, included UNAN-Leon had a lack of simulation skill lab, equipment, and space, whereas ECU CON had sufficient resources. The ECU school lacked applied case studies from a rural health medical-surgical adult nursing perspective and less time in rural health clinics. The UNAN-Leon nursing standards generalized based on the Ministry of Health (MINSA) and the US program was specific based on the American Nurses Association and various sub-specialties of nursing practice requirements. The CE Model was a useful framework to facilitate a collaborative partnership. Conclusion: Collaborative evaluation study using the International Nursing Education Curriculum Evaluation Tool can be an effective method to evaluate medical and surgical curricula similarities and differences within international nursing schools. The Community Engagement Model fostered a faculty partnership. Highlights: Curriculum Evaluation Study between Nicaragua and US Nursing Schools Conducted simultaneous assessment, and analysis of (adult) med-surgical curriculum Nicaragua & US Nursing School had similar adult nursing curriculum, however US utilized more technology simulation labs and Nicaragua conducted more rural /city clinic case studies and clinical practicums. This international collaborative successfully utilized the Community Engagement Model